KISAH KAUM NABI LÛTH DALAM AL-QUR’AN DAN RELEVANSINYA TERHADAP PERILAKU PENYIMPANGAN SEKSUAL - Santi Marito (Yurisprudentia: Jurnal Hukum Ekonomi, 2019)
This research is motivated by the increasingly widespread existence of homosexuals; this is evidenced by their increasing number every year. In 2015 the Indonesian Ministry of Health noted that there were 25,412 cases of homosexuals infected with HIV, in 2016 reaching 28,640 cases. In addition, homosexuals and their supporters try to legalize fellow marriages. They use the jargon "Indonesia without discrimination" to be the entrance to legalize same sex marriage and they review all state policies that threaten criminal law and discriminate against their groups. This research is library research. The primary data source in this study is the Tafsir Al-Qur'an al-Azhim interpretation, while the secondary sources used are books, scientific journal, papers, articles and scientific works that are relevant to this research. The method used in this study is Maudhu'i interpretation method while data analysis uses descriptive analysis. The results of this study reveal several discoveries, namely: (1) the story of the Prophet in the Koran according to Ibnu Katsir perspective includes: the names and phrases of the Lûth prophet, the first homosexuals, the Lûth prophet belied their prophet, the Prophet Lûth harapanth was lost hope, the angel came to the house of the Prophet Luth  in the form of a handsome man, the people of the Prophet Lûth came to the house of the Prophet and their land was made a useless lake. Homosexuality in the story of the Lûth Prophet's people is interpreted by Ibnu Katsir by liking same-sex men who like men and women like women who are now known as gay and lesbian. (2) the relevance of the story of the Prophet people with sexual deviance behavior in modern times is that they both love handsome men, both have a place of association, are equally afraid of the punishment of God, both have no interest in the opposite sex, both have enough economy.